The Influence of Malaqbiq Cultural Values on Narcotics Abuse Prevention in Majene Regency - Anwar, M. Chaerul; Yasim, Sulastri (Jurisprudentie : Jurusan Ilmu Hukum Fakultas Syariah dan Hukum, 2025)
This study aims to analyze the role of Malaqbiq cultural values in the prevention of narcotics abuse in Majene Regency through a socio-cultural approach. Malaqbiq, which emphasizes personal honor, shame toward immoral behavior (siri’), and collective responsibility, functions as a form of informal social control that can shape moral awareness and preventive behavior, particularly among the younger generation. This research employs an empirical legal method with a qualitative approach, using observation, interviews, and document analysis. The findings show that the internalization of Malaqbiq values within families, customary communities, and education holds great potential in strengthening social resilience against drug abuse. However, these values are increasingly eroded by globalization, digital media, and the weakening of traditional socialization agents. Meanwhile, Law Number 35 of 2009 concerning Narcotics provides a comprehensive legal framework but requires reinforcement through local wisdom-based strategies to ensure more effective prevention. Integrating Malaqbiq values into educational programs, public outreach, and regional policies is recommended as a contextual and sustainable approach in combating narcotics abuse in Majene. This study underscores the importance of balancing formal legal mechanisms with culturally grounded preventive models to address the complex challenges of drug-related crime in contemporary Indonesian society.